Epidemiological investigation of venomous snakebites in Yunnan Province - Gao, Qinfen; Teng, Yajun; Xiao, Chao; Zeng, Rui; Han, Bin; Gao, Hong; Wang, Jianhai; Li, Xiaoyan; Yang, Canju; Dai, Jianneng; Li, Chunxi; Huang, Qunyan; et al. (Frontiers in Toxicology, 2025)
BackgroundSnakebite envenoming constitutes a substantial public health concern worldwide. Yunnan Province, The lack of comprehensive epidemiological data on snakebite in Yunnan affects research, diagnostic, and treatment advancements. This research evaluates patient demographics, seasonal patterns, snake species associated with the disease, and treatment approaches to guide preventative and therapeutic initiatives in the province.MethodsThis retrospective analysis reviewed clinical records of venomous snakebite cases admitted to hospitals in 16 cities within Yunnan Province from January 2022 to November 2024. Collected data covered diverse aspects, including patient demographics (age, sex), circumstances of the bite (location, size, and time), species identification, observed clinical symptoms, treatments administered (e.g., antivenin and alternative therapies), and hospital stay duration. Subsequently, the effect of different therapeutic measures on these patients’ hospital stays was analyzed.ResultsA total of 2,112 venomous snakebite cases were recorded, with incidence rates rising annually: 406/46.73 million in 2022, 825/46.73 million in 2023, and 886/46.73 million in 2024. Ovophis (52.08%) and Trimeresurus (28.74%) species were predominant. These findings align with the annual distribution of anti-venom serum administered to affected individuals. Most incidents occurred during June to September, primarily in mountainous and forested areas or paddy fields, comprising approximately 52.40% of the total cases. Nearly all bites (99.05%) were localized to the limbs, presenting with swelling and pain as the dominant clinical features. Statistical analysis revealed that factors such as incision and debridement, additional anti-venom serum, fibrinogen supplementation, plasma administration, Ji Desheng Snake Medicine, and magnesium sulfate compresses were significantly associated with extended hospital stays (P < 0.05).ConclusionSnake bites in Yunnan Province mainly affect young and middle-aged agricultural workers in rural and mountainous areas. The predominant venomous snakes in the area are hemotoxic. The findings emphasize the necessity of early intervention with antivenom and adjunctive therapies, including fibrinogen and plasma administration. Delays in getting medical help or improper treatment can lead to longer hospital stays.